2016
DOI: 10.1016/j.jsbmb.2016.05.019
|View full text |Cite
|
Sign up to set email alerts
|

The UVB1 Vitamin D analogue inhibits colorectal carcinoma progression

Abstract: Vitamin D has been shown to display a wide variety of antitumour effects, but their therapeutic use is limited by its severe side effects. We have designed and synthesized a Gemini vitamin D analogue of calcitriol (UVB1) which has shown to display antineoplastic effects on different cancer cell lines without causing hypercalcemia. The aim of this work has been to investigate, by employing in silico, in vitro, and in vivo assays, whether UVB1 inhibits human colorectal carcinoma progression. We demonstrated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
2
5
0
Order By: Relevance
“…6 A and B). As expected in light of our previous results [34] hydrogen bond interactions between calcitriol and Tyr143, Ser237,…”
Section: Computational Studiessupporting
confidence: 91%
See 1 more Smart Citation
“…6 A and B). As expected in light of our previous results [34] hydrogen bond interactions between calcitriol and Tyr143, Ser237,…”
Section: Computational Studiessupporting
confidence: 91%
“…presents the corresponding energies for each interaction component for calcitriol and ML-344 at both pH values.From the analysis of calcitriol component, no significant differences were observed regarding the affinity for VDR at both pH values. In agreement with our previous reports[30,34], the binding of calcitriol at both pHs is mainly stabilizedby Van der Waals interactions (-60.1 and -63.5 Kcal/mol at pH 5.5 and 7, respectively), with a lesser contribution of the EEL component (-33.2 and -27.2…”
supporting
confidence: 93%
“…Particularly, a range of VDR ligands displays a pro-apoptogenic activity—an active metabolite of vitamin D, 1α,25(OH) 2 D 3 , was found to increase Bax/Bcl-2 ratio in leukemia cells [45] and trigger cytochrome c release from mitochondria with subsequent activation of caspase cascade in prostate cancer cells [46]. Apoptosis-inducing activity of VDR ligands was also shown for the Gemini vitamin D analogue of 1α,25(OH) 2 D 3 [47] and diarylmethane skeleton-containing VDR agonist [48] in colon and breast cancer cells, respectively. Beside this, activation of VDR can stimulate autophagy—previously, it was found that 1α,25(OH) 2 D 3 and calcipotriol induce autophagy in breast and colorectal cancer [44,49] and cervical carcinoma [50] cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We had previously demonstrated that the analogues UVB1 and EM1 decreased cell viability of cell lines coming from different tumor types (colon cancer, head and neck squamous cell carcinoma, glioblastoma multiforme) [12,13,15,16]. Additionally, EM1 displayed anti-metastatic effect [14] in an animal model developed from hormone-independent HER2-positive LM3 cell line, which is derived from a murine mammary adenocarcinoma [19].…”
Section: Vitamin D Analogues Uvb1 and Em1 Reduce Cell Viability Of Human Her2positive Bc Cell Linesmentioning
confidence: 99%
“…Our group has synthetized two novel non-hypercalcemic vitamin D analogues, UVB1 and EM1, that have demonstrated promising antitumor effects in preclinical studies employing cell lines cultured under 2-dimensional (2D) conditions and in vivo models generated from these cells [12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%